2003
DOI: 10.1076/jcen.25.7.949.16482
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Visual Memory Deficits in Schizophrenia and Bipolar Psychoses Using the Rey-Osterrieth Complex Figure: Effects of Duration of Illness

Abstract: Verbal declarative memory deficits in schizophrenia are well documented whereas visual declarative memory is less studied. Moreover, there are limited data on whether organizational and visual memory deficits are specific to schizophrenic psychoses. We compared visual memory and organizational function in patients with chronic schizophrenia (n=79) and chronic bipolar psychotic disorder (n=14), and in healthy controls (n=84) using the Rey-Osterrieth Complex Figure (ROCF), testing whether organizational impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 0 publications
6
55
1
4
Order By: Relevance
“…Our previous study showed that the visual cortex of type 2 diabetic patients revealed disrupted resting-state amplitude of low-frequency fluctuations and regional homogeneity (38). We speculate that the decreased functional connectivity to the visual cortex lowers the performance in the CFT delayed recall test that is related to visual memory (39). The precentral gyrus is reportedly an important motor area that is atrophic in patients (19).…”
Section: Discussionmentioning
confidence: 86%
“…Our previous study showed that the visual cortex of type 2 diabetic patients revealed disrupted resting-state amplitude of low-frequency fluctuations and regional homogeneity (38). We speculate that the decreased functional connectivity to the visual cortex lowers the performance in the CFT delayed recall test that is related to visual memory (39). The precentral gyrus is reportedly an important motor area that is atrophic in patients (19).…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, there are limited data on whether organizational and visual memory deficits are specific to schizophrenic psychoses. Seidman et al (2003) compared visual memory and organizational function in patients with chronic schizophrenia (n=79) and chronic bipolar psychotic disorder (n=14), and in healthy controls (n=84) using the Rey-Osterrieth Complex Figure (ROCF), testing whether organizational impairments (i.e., executive dysfunctions) account for the visual memory deficit. Groups were comparable on age, handedness and expected intellectual ability (based on single word reading).…”
Section: Introductionmentioning
confidence: 99%
“…Visual memory impairments on the ROCFT have been well-documented among people with schizophrenia, and are influenced by the use of poor organizational strategies [28][29][30]. Thus, the ROCFT is an excellent candidate for adaptation as an LP measure, in which test-takers are provided with the opportunity to learn an organizational strategy.…”
Section: Introductionmentioning
confidence: 99%